Pediatric ECMO Research: The Case for Collaboration - Bembea, Melania M.; Hoskote, Aparna; Guerguerian, Anne-Marie (Frontiers in Pediatrics, 2018)
The use of extracorporeal membrane oxygenation (ECMO) in the pediatric age has increased considerably in the last decade, as has the complexity of cases and the variety of indications outside of the neonatal age. However, no randomized controlled trials have been attempted to date to test ECMO as an intervention in non-neonatal pediatric patients with critical illness. In this review, we provide a brief overview of the history of clinical research in pediatric ECMO and discuss methodological challenges including heterogeneity of ages and diagnoses in the pediatric ECMO population, rapid advances in technology and clinical practice related to ECMO, feasibility of enrolling critically ill children on ECMO in clinical research studies, and variability in ECMO management across institutions and countries. Lastly, we discuss opportunities and existing infrastructure for future multicenter, multi-network research collaborations for pediatric ECMO studies.